2023
DOI: 10.1007/s40264-023-01286-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of European Union Label Changes for Fluoroquinolone-Containing Medicinal Products for Systemic and Inhalation Use: Post-Referral Prescribing Trends

Abstract: Introduction Concerns of the persistence and severity of the adverse effects of fluoroquinolones, mainly involving the nervous system, muscles and joints, resulted in the 2018 referral procedure led by the European Medicines Agency (EMA). They advised to stop prescribing fluoroquinolones for infections of mild severity or of a presumed self-limiting course and for prevention of infections, plus to restrict prescriptions in cases of milder infections where other treatment options are available, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…Although this study is reported in the MHRA Drug Safety Update as showing ‘no change’ in prescribing, it does show a reduction in fluoroquinolone prescribing, and is estimated by Ly et al to be “at best, a reduction in prescriptions of around 25%”. 15 As such, our results are concordant and extend the study period and show further reductions since then. The English Surveillance Programme for Antimicrobial Utilisation and Resistance (ESPAUR) report for 2023 provides supportive data, with quinolone prescription dropping from 0.565 in 2018 to 0.456 in 2022 (p = 0.04).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Although this study is reported in the MHRA Drug Safety Update as showing ‘no change’ in prescribing, it does show a reduction in fluoroquinolone prescribing, and is estimated by Ly et al to be “at best, a reduction in prescriptions of around 25%”. 15 As such, our results are concordant and extend the study period and show further reductions since then. The English Surveillance Programme for Antimicrobial Utilisation and Resistance (ESPAUR) report for 2023 provides supportive data, with quinolone prescription dropping from 0.565 in 2018 to 0.456 in 2022 (p = 0.04).…”
Section: Discussionsupporting
confidence: 85%
“…It was not able to identify a reduction in fluoroquinolone usage directly in relation to the EMA guidance. 15 However, this study did show that a) the UK had the lowest rates of fluoroquinolone prescribing in all included countries, and b) the UK had around a 3% reduction per year in fluoroquinolone prescriptions from 2016 to 2020 guidance. 15…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the year to August 2023, over 450 000 primary care prescriptions for oral fluoroquinolones were dispensed in England with a threefold variation in the volume of prescribing across Integrated Care Boards 5. A retrospective population-based cohort study of electronic health records across several European countries found that changes in fluoroquinolone prescribing did not seem to be temporally related to the safety alerts issued in 2019 6…”
Section: Contextmentioning
confidence: 99%